Exercise Program: Tai Chi and Cognitive Stimulation to Improve Health Status of Elderly in Nursing Homes - Ni Made Riasmini; Eska Riyanti; I Wayan Suardana; I Ketut Gama; Husnul Khatimah (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2021)
The structure of the aging population reflects the higher average life expectancy, which possesses an impact on the emergence of degenerative non-communicable diseases. Promotive effort through an exercise program (tai-chi exercise and cognitive stimulation) is required for the elderly to enhance their physical and mental health. This study aims to determine an overview of the exercise program's effectiveness on the health status of the elderly in nursing homes. The research method administered Quasi experiment with a control group design. The sample was the elderly who live in nursing homes. This study employed simple random sampling with a total sample of 116 people in 2 provinces: DKI Jakarta and South Sumatra Province. The statistical test utilized a t-test and multiple linear regression test. The results revealed that there was a difference in the average value of the health status of the elderly before and after the exercise programs in the intervention group (p-value = 0.001), there was a difference in the average value of the health status of the elderly between the intervention group and the control group after the exercise intervention program (p-value = 0.001), there was a relationship between the length of stay in the orphanage on the health status of the elderly. Recommendation: the resulting exercise program can be employed as complementary therapies replicated more extensively in various health care settings.